KONSEP JAMINAN SOSIAL DALAM SISTEM EKONOMI ISLAM (Analisis Terhadap Istilah TakÄful al-IjtImÄâ€™Ã®, DamÄn al-IjtImÄâ€™Ã® dan Taâ€™min al-IjtimÄâ€™Ã®) - Alfin, Aidil (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2011)
Concept of social security in Islam is different than conventional concept of social security. Social security in Islam is the basic life assurance to meet the economic necessities of the community in most minimal standard for all members of society. This Notion is in line with term damÄn al-ijtimÄâ€™Ã®. Responsibility for implementation is not only a state duty, but also all members of society. They are integrally responsible for achieving this goal, as the purpose is contained in the term takaful al-ijtimai.